Penggunaan refrigeran hidrokarbon MC-134 pada mesin freezer untuk pedagang es krim keliling - I Dewa Made Susila; Daud Simon Anakottapary; I Wayan Adi Subagia; Putu Wijaya Sunu; I Nengah Ardita (Journal of Applied Mechanical Engineering and Green Technology, 2022)
This study aims to determine the performance and energy consumption of the freezer machine for mobile ice cream sellers using the environmentally friendly MC134 refrigerant with a compressor capacity of 1/10 HP. This research was conducted using an experimental method. The size of the capillary tube is determined using the Cap Tube 1.0.8.0 application program. The evaporator used is a bare tube type that is wrapped around an ice cream box. The test is carried out by measuring the temperature and pressure of the refrigerant, the temperature in the ice cream box, as well as the electric current and voltage in the system. The results of the analysis of performance and energy consumption will also be compared if the system uses HFC134a refrigerant. From the test results obtained the optimum mass that is filled into the system for MC134 refrigerant is 155 grams and the optimum mass for 134a refrigerant is 202 grams. The use of MC134 refrigerant is more efficient by 23.3%. The COP for MC134 refrigerant is 3.1 while the COP for 134a refrigerant is 2.7. The energy consumption for MC134 is 67.8 kJ while for R134a is 83 kJ.